Multidimensional contractile reserve predicts adverse outcome in patients with severe systolic heart failure: a 4‐year follow‐up study. (21st February 2017) - Paraskevaidis, Ioannis A.; Ikonomidis, Ignatios; Simitsis, Panagiotis; Parissis, John; Stasinos, Vasilios; Makavos, George; Lekakis, John
Abstract: Aims: Left ventricular contractile reserve is a prognostic indicator for adverse outcome in patients with severe chronic heart failure with reduced ejection fraction (HFrEF). We investigated the dobutamine‐induced changes of LV multidimensional deformation and their predictive value for cardiac mortality of patients with severe chronic HFrEF. Methods and results: In this prospective study, out of 130 patients with severe HFrEF who underwent a low‐dose dobutamine stress echocardiography (LDSE) study using speckle tracking imaging, 100 patients were followed up for the occurrence of cardiac death over a period of 4 years. Compared with survivors, non‐survivors ( n = 32) had lower radial strain (RS) and strain rate (RSR) (10.7 ± 5.9 vs. 20.1 ± 8% and 0.5 ± 0.2 vs. 0.8 ± 0.3 L/s, P < 0.001), a smaller increase of global longitudinal strain (GLS) and strain rate after LDSE (0.9 ± 1.5 vs. –3.3 ± 3.5% and −0.1 ± 0.1 vs. –0.3 ± 0.3 L/s, P < 0.001), and a lack of change in the circumferential and radial deformation. The dobutamine‐induced changes of all speckle tracking indices predicted cardiac mortality, while, among resting echocardiographic parameters, only RS and RSR predicted survival, after adjusting for age, sex, cardiomyopathy aetiology, NYHA class, AF, BNP levels, resting LVED, and LV outflow tract velocity–time integral, and their respective changes produced by dobutamine ( P < 0.05). The dobutamine‐induced change of GLS and resting RS were the best additive predictors of mortality with a net reclassification improvement of 0.518 ( P = 0.022) Conclusion: In severe chronic HFrEF, resting RS and the dobutamine‐induced change of GLS are independent predictors of cardiac mortality.